Digitalisasi Bisnis Syariah: Peluang Baru bagi Womenpreneur - Desy Arum Sunarta (Mappideceng:Jurnal Ekonomi Syariah, 2024)
The development of digital technology has created great opportunities for womenpreneurs to develop sharia businesses. This research aims to analyze how digitalization can empower womenpreneurs to increase income, expand market reach, and contribute to sharia economic growth. The research method used is a literature review. The research results show that digitalization has had a positive impact on sharia businesses managed by womenpreneurs, but there are still several challenges that need to be overcome.